Γ-Cyclodextrin-based polypseudorotaxane hydrogels for ophthalmic delivery of flurbiprofen to treat anterior uveitis. (1st February 2022) - Fang, Guihua; Wang, Qiuxiang; Yang, Xuewen; Qian, Yu; Zhang, Guowei; Tang, Bo
Abstract: Anterior uveitis is a sight-threatening inflammation inside the eyes. Conventional eye drops for anti-inflammatory therapy need to be administered frequently owing to the rapid elimination and corneal barrier. To address these issues, polypseudorotaxane hydrogels were developed by mixing Soluplus micelles (99.4 nm) and cyclodextrins solution. The optimized hydrogels exhibited shear-thinning and sustained release properties. The hydrogels exhibited higher transcorneal permeability coefficient (Papp, 1.84 folds) than that of drug solutions. Moreover, animal study indicated that the hydrogels significantly increased the precorneal retention (AUC, 21.2 folds) and intraocular bioavailability of flurbiprofen (AUCAqueous humor, 17.8 folds) in comparison with drug solutions. Importantly, the hydrogels obviously boosted anti-inflammatory efficacy in rabbit model of endotoxin-induced uveitis at a reduced administration frequency. Additionally, the safety of hydrogels was confirmed by cytotoxicity and ocular irritation studies. In all, the present study demonstrates a friendly non-invasive strategy based on γ- CD-based polypseudorotaxane hydrogels for ocular drug delivery. Graphical abstract: Preparation of γ-cyclodextrin-based polypseudorotaxane hydrogels and topical delivery of FLB for the treatment of anterior uveitis. Unlabelled Image